Iterated non-linear model predictive control based on tubes and contractive constraints. (May 2016) - Murillo, M.; Sánchez, G.; Giovanini, L.
Abstract: This paper presents a predictive control algorithm for non-linear systems based on successive linearizations of the non-linear dynamic around a given trajectory. A linear time varying model is obtained and the non-convex constrained optimization problem is transformed into a sequence of locally convex ones. The robustness of the proposed algorithm is addressed adding a convex contractive constraint. To account for linearization errors and to obtain more accurate results an inner iteration loop is added to the algorithm. A simple methodology to obtain an outer bounding-tube for state trajectories is also presented. The convergence of the iterative process and the stability of the closed-loop system are analyzed. The simulation results show the effectiveness of the proposed algorithm in controlling a quadcopter type unmanned aerial vehicle. Abstract : Highlights: Predictive control algorithm for non-linear systems. Addition of contractive constraints to the optimization problem to guarantee the stability issues. Proposal of a simple methodology to achieve outer bounding-tubes for state trajectories. Simulation results for short and long prediction horizons are shown.